South African medical interns’ perspectives on the use of point of care ultrasound - Pierre-Andre Mans; Oladele V. Adeniyi (South African Family Practice)
Background: Point of care ultrasound (POCUS) has become such a part of patient care that it is included in undergraduate medical training in many high-income countries. In South Africa, despite the availability of ultrasound units, there is no information on the exposure or training required for medical interns to perform POCUS in their community service year. This study examines interns’ self-reported POCUS training and competency, as well as their perceived readiness for their community service year.